2015
DOI: 10.5455/jeos.20150105105524
|View full text |Cite
|
Sign up to set email alerts
|

Trace Metal Contamination in Tropical Endemic Fish: Factorial Effect Interactions and In situ Quantitative Risk Assessment

Abstract: Aim: Contamination of the Anambra River with heavy metals (arsenic, As; cadmium, Cd; chromium, Cr; copper, Cu; lead, Pb; nickel, Ni; and zinc, Zn) was examined in two preponderant fish species (Synodontis clarias and Tilapia nilotica) following earlier detection of the elements in water column. Methods: Levels of heavy metals were measured in both seasonal regimes (rainy and dry) at five selected locations with atomic absorption spectrophotometer. Factorial effects and interactions were explored on completely … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 44 publications
1
3
0
Order By: Relevance
“…Furthermore, some other aquatic animals may have accumulated these chemicals in their bodies from other habitats, and have overtime migrated to the water body sampled in this study. The concentration of PAHs and BTEX recorded in this work is similar to those reported by other researchers [50,51]. In their study, Akinsanya et al [52] reported a concentration of 49.86±7.30 μg/L and 173.34±4.677 μg/g for BTEX and PAHs respectively as they bioaccumulate in the intestine of Heterotis niloticus.…”
Section: Discussionsupporting
confidence: 90%
“…Furthermore, some other aquatic animals may have accumulated these chemicals in their bodies from other habitats, and have overtime migrated to the water body sampled in this study. The concentration of PAHs and BTEX recorded in this work is similar to those reported by other researchers [50,51]. In their study, Akinsanya et al [52] reported a concentration of 49.86±7.30 μg/L and 173.34±4.677 μg/g for BTEX and PAHs respectively as they bioaccumulate in the intestine of Heterotis niloticus.…”
Section: Discussionsupporting
confidence: 90%
“…Target hazard quotient (THQ) used to characterise oral metal exposure and chronic noncarcinogenic risk was conducted following established methods and assumptions [2,7,[20][21][22][23][24][25]: MC = metal mean concentration (mg kg −1 ), IR = the daily ingestion rate (adult) (0.04 kg), EF = the exposure frequency (365 days/year), ED = the exposure duration for noncarcinogens (…”
Section: Exposure and Noncarcinogenic Risk Assessmentmentioning
confidence: 99%
“…There has been a growing community concern among residents within riverine areas of Anambra State Nigeria about the potential contamination of freshwater ecosystems that hold critical livelihood economics of the community through fish trade. A body of empirical research in River Niger and Anambra River, the largest freshwater ecosystems in the state, has shown the degree to which the systems are contaminated with appreciable metal concentrations that potentially pose public health risks to freshwater food consumers [1][2][3][4][5]. The river sites studied represent zones of unregulated waste disposal and human activities that threaten ecology of those freshwater systems.…”
Section: Introductionmentioning
confidence: 99%
“…According to literature, fish's position in the trophic transfer of heavy metals through the aquatic food chain and food menu (Fig. 1) poses a higher risk to public health (Levit, 2010;Obiakor et al, 2015).…”
Section: Occurrence and Impact Of Heavy Metals In The Environmentmentioning
confidence: 99%